(E, E)‐1, 1′‐[1, 2‐Bis(4‐chlorophenyl)ethane‐1, 2‐diyl]bis(phenyldiazene) revisited: threefold configurational disorder of (S, S), (R, R) and (S, R) isomers, a detailed critique. Issue 3 (15th February 2023) - Parkin, Sean; Glidewell, Christopher; Horton, Peter N.
Abstract : A distorted structure originally described as a monoclinic polymorph of meso ‐( E, E )‐1, 1′‐[1, 2‐bis(4‐chlorophenyl)ethane‐1, 2‐diyl]bis(phenyldiazene) is better modeled as a threefold superposition of undistorted S, S and R, R enantiomers with a smaller fraction of the meso isomer. All reasoning behind the reassessment is explained in detail. Abstract : Crystal structures described as concomitant triclinic (I ) and monoclinic (II ) polymorphs of meso ‐( E, E )‐1, 1′‐[1, 2‐bis(4‐chlorophenyl)ethane‐1, 2‐diyl]bis(phenyldiazene) [Mohamed et al. (2016). Acta Cryst . C72, 57–62] have been re‐investigated. The published model for II was distorted due to forcing the symmetry of space group C 2/ c on an incomplete structure model. It is shown here to be a likely three‐component superposition of S, S and R, R enantiomers with a lesser amount of the meso form. A detailed analysis of how the improbable distortion in the published model aroused suspicion and the subsequent construction of undistorted chemically and crystallographically plausible alternatives having the symmetry of Cc and C 2/ c is presented. For the sake of completeness, an improved model for the triclinic P structure of the meso isomer I, revised to include a minor disorder component, is also given.